C.1 - India. Administration Reforms Commission (Delhi, 1967)
The Study Team on "Economic Administration" which was set up by the Administrative Reforms Commission in May, 1966, to ascertain facts, locate problem areas and make suitable recom mendations, has finished its task. In a task of this nature, the limita tion of time invariably has its impact on the scope of enquiry and the methodology used. In a field like Economic Administration, the impact has been all the greater owing to the enormous number of points where Government comes in contact with industry, trade and commerce. We have, therefore, made a deliberate choice of such sectors of economy and instruments of Government regulations which, in our view, have a strategic importance in the process of economic development. While we have mainly concerned ourselves with the problems of administration, steering clear of basic policies, it has not always been possible to refrain from expressing com ments on the appropriateness of the strategies employed by the Government in economic administration. Having taken the Govern ment's basic objectives for granted, we have felt free to express our opinion on the soundness or otherwise of the administrative devices and mechanisms adopted for achieving them. We have also made concrete suggestions regarding alternative administrative arrange ments which, we feel, will achieve these objectives more effectively and more speedily. The consideration of the administrative cost versus the benefit conferred on society has been constantly kept in view.
Keywords: India - Economic conditions